2021
DOI: 10.3390/foods10061172
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Talk: A Qualitative Study Exploring Attitudes towards Sugar, Sweeteners and Sweet-Tasting Foods in the United Kingdom

Abstract: Worldwide initiatives currently aim to reduce free sugar intakes, but success will depend on consumer attitudes towards sugar and the alternatives. This work aimed to explore attitudes towards sugar, sweeteners and sweet-tasting foods, towards consumption and related policies, in a sample of the general public of the UK. Focus groups and interviews were conducted with 34 adults (7 males, ages: 18–65 years). Thematic analysis identified six themes: ‘Value’ (e.g., pleasure, emotions), ‘Angle’ (e.g., disinterest)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Less interest in purchasing a fruit and cereal bar with health-promoting properties was found when the sugar content of the product was reduced, even though such a modification was one of the most expected by respondents. These results indicate that although respondents declared that they expected such changes, they were not ready to purchase such products, perhaps because they still associate bars with a “sweet snack” and, as indicated by [ 52 ], this may be due to consumers being used to the sweet taste and not being willing to change their habits. It is noted that the snack industry, meeting the expectations of consumers as well as doctors and nutritionists, is looking for innovative alternatives to the sugar-reduced cereal bar.…”
Section: Discussionmentioning
confidence: 99%
“…Less interest in purchasing a fruit and cereal bar with health-promoting properties was found when the sugar content of the product was reduced, even though such a modification was one of the most expected by respondents. These results indicate that although respondents declared that they expected such changes, they were not ready to purchase such products, perhaps because they still associate bars with a “sweet snack” and, as indicated by [ 52 ], this may be due to consumers being used to the sweet taste and not being willing to change their habits. It is noted that the snack industry, meeting the expectations of consumers as well as doctors and nutritionists, is looking for innovative alternatives to the sugar-reduced cereal bar.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on the health impacts of artificial sweeteners is novel, evidence has consistently questioned their safety for children (10)(11)(12)(13) and, more recently, for adults (14) . Studies among adults (31) , parents (32,33) and children (33) have suggested that sweeteners are generally perceived as unhealthful due to their synthetic origin, carcinogenic and addictive potential. In line with these perceptions, our data showed that a high proportion of adults and adolescents believed children should not consume products with sweeteners.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence on the negative health effects of artificial sweeteners’ intake is accumulating, such as the association with cardiovascular disease and mortality [ 59 ], and with increased cancer risk [ 60 ]. Unfortunately, many in the general public still adopt the use of sweeteners as a short-term strategy to reduce dietary sugar and for weight management [ 61 ].…”
Section: Discussionmentioning
confidence: 99%